Interpreting Globalization : Polish Perspectives on Culture in the Globalized World - Koczanowicz, Leszek,; Fereński, Piotr Jakub,; Panciuchin, Joanna, (Value Inquiry Book Series ;, 2021)
The main hypothesis of the volume is that globalization is a cultural phenomenon. Therefore, the book offers an explanation of how globalization emerged from cultural exchange between groups, nations, and religions. The articles in this volume register the thematically multi-dimensional and theoretically complex contribution of Polish research on globalization. Polish debates on globalization, as presented in this book, on the one hand reflect international disputes and controversies, and on the other hand address local issues. As their crucial feature, the articles in this volume exhibit a special sensitivity to historical and contemporary cultural contexts. They do not approach globalization as an abstract process, instead exploring it through the lens of clearly defined factors.